Hemingway's genders : rereading the Hemingway text - Comley, Nancy R. (Yale University Press, 1994)
Ernest Hemingway has long been regarded as a fiercely heterosexual writer who advocated and embodied an exaggerated masculinity. This witty and intelligent book, the first to focus exclusively on gender in Hemingway's writing, presents a new view of the author, demonstrating that issues of gender and sexuality are more complex and subtle in his work than has ever been imagined.